Pengaruh Terapi Musik Klasik terhadap Intensitas Nyeri pada Inpartu Fase Aktif Kala I Persalinan di Praktek Mandiri Bidan Pertiwi Sengkang Kabupaten Wajo - Warlinda Warlinda; Yusda Seman MY; Enggar Enggar (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
This study aims to determine the effect of classical music therapy on pain intensity in active phase in-partu mothers during the first stage of labor at the Independent Midwife Practice of Pertiwi Sengkang, Wajo Regency. This type of research is quantitative research using the Pre-experimental design method "One Group pretest - posttest design". The sampling technique used in this study used total sampling with a total sample of 30 mothers giving birth at the Pertiwi Sengkang Midwife Independent Practice, Wajo Regency, while data analysis used the Wilcoxon Signed Rank test. The results of the study showed a p-value of 0.000 (p <0.05) which means that the alternative hypothesis is accepted. This means that the alternative hypothesis is that there is an effect of classical music therapy on pain intensity in active phase in-partu mothers during the first stage of labor at the independent practice of midwives in Pertiwi Sengkang, Wajo district. By him, it is hoped that health workers, especially midwives as birth attendants, can help mothers in childbirth to meet their needs for comfort in controlling pain and can use classical music therapy in the delivery process which helps mothers in labor to reduce pain during labor.